Feasibility Analysis of Joyful Learning Implementation through Digital Technology Integration: Challenges and Solutions - Islahuddin; Winarti; Sulisworo, Dwi (The Indonesian Institute of Science and Technology Research, 2025)
The rapid advancement of digital technology has enabled the implementation of Joyful Learning, an innovative approach that enhances student engagement, motivation, and comprehension. Grounded in multiple pedagogical frameworks—Constructivism, Meaningful Learning, Flow Theory, and Multiple Intelligences—Joyful Learning emphasizes interactive, student-centered education. This study employs a conceptual analysis approach to assess the feasibility of Joyful Learning in digital learning environments by identifying key implementation challenges, including traditional teaching paradigms misaligned with digital-native learners, rigid curricula, outdated assessment methods, limited teacher readiness, and inadequate technological infrastructure. By synthesizing theoretical perspectives with digital learning strategies such as AI-driven personalization, gamification, and adaptive assessment, this study offers practical solutions for overcoming these barriers. The findings underscore the necessity of interdisciplinary collaboration, professional development for educators, and enhanced digital infrastructure to facilitate the effective integration of Joyful Learning. While digital technology presents transformative opportunities, its successful application depends on systemic support and policy alignment. Future research should explore long-term learning outcomes and adaptability across diverse educational contexts.